SOUNDSCAPE PERIBADATAN DALAM EVALUASI AKUSTIKA RUANG STUDI KASUS MASJID RAYA MUJAHIDIN PONTIANAK - Imanuel, Imanuel; Lubis, Mira Sophia; Zain, Zairin (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
Soundscape or room acoustics is a branch of building physics that focuses on the condition, movement, or quality of acoustics or sound in a space. Soundscape can be divided into 2 main parts, one focusing on open spaces, and one on closed spaces. Open spaces that we usually find are parks, streets, roundabouts, performance stages, or outdoor concerts. The Mujahidin Grand Mosque is one of the largest places of worship in Pontianak City. As a grand mosque, of course, the quality of indoor acoustics that it requires must be good and adequate. However, there is an issue among mosque users who say that the acoustic quality of the Mujahidin Grand Mosque is not good, because, in several places in the main worship area of the mosque, there is noise interference. This interference is in the form of echoes or reverberations in certain areas, especially around the stairs and openings. Therefore, an evaluation of the acoustic quality of the worship space of the Mujahidin Grand Mosque in Pontianak is needed. This study focuses on the acoustic quality of the main worship space of the Mujahidin Grand Mosque. The study was conducted using software assistance in the form of Ecotect Analysis and Ease Focus III. From the research conducted, it was found that the acoustic quality of the object was far above standard. With an average noise level of 60.5 dB, and a reverberation time of 5.13 seconds. The biggest acoustic problems are in the area adjacent to the opening, the front area of the shaft, and the middle area of the room.